Talang buhay ng Supremo And. Bonifacio sa Kabite Supremo Andres Bonifacio in Cavite - Aguinaldo, Emilio 1869-1964 (National Historical Commission of the Philippines, 2020)
On biography of Andres Bonifacio in Cavite, Philippines.